Advances in covalent organic frameworks in separation science - Qian, Hai-Long; Yang, Cheng-Xiong; Wang, Wen-Long; Yang, Cheng; Yan, Xiu-Ping (Journal of Chromatography A, 2018)
[Display omitted] •Applications of covalent organic frameworks for sample preparation are reviewed.•Applications of covalent organic frameworks for chromatography are reviewed.•The prospects of COFs for separation science are presented. Covalent organic frameworks (COFs) are a new class of multifunctional crystalline organic polymer constructed with organic monomers via robust covalent bonds. The unique properties such as convenient modification, low densities, large specific surface areas, good stability and permanent porosity make COFs great potential in separation science. This review shows the state-of-the art for the application of COFs and their composites in analytical separation science. COFs and their composites have been explored as promising sorbents for solid phase extraction, potential coatings for solid phase microextraction, and novel stationary phases for gas chromatography, high-performance liquid chromatography and capillary electrochromatography. The prospects of COFs for separation science are also presented, which can offer an outlook and reference for further study on the applications of COFs.